Control of foliar rusts of wheat in South Africa with special emphasis on Puccinia striiformis f. sp.Tritici - Boshoff, Willem Hendrik Petrus (University of the Free State, 2000)
English: Stripe rust, caused by Puccinia striiformis Westend. f. sp. tritici Eriks., has become an endemic disease of wheat (Triticum aestivum L.) in South Africa after being observed for the first time near Moorreesburg, Western Cape, during August 1996. Pathotypes (pts.) detected in surveys were 6E16A- with virulence to Yr2,6,7,8,11,14,17 and Yr19, and 6E22A- with added virulence to Yr25. Stripe rust isolates found on Hordeum murinum L. in the Western Cape were identified as pt. 6E 16A- whereas both pts. 6E 16A- and 6E22A- were collected from Bromus catharticus Vahl in the eastern Free Sate. The possible role that grass species may play in the over-summering of the stripe rust pathogen has not yet been fully established. However, stripe rust infections have been found on summer-sown wheat in the south Western Cape during 1998, volunteer wheat growing in the summer and autumn months in the eastern Free State from 1998 to 2000, and on summer-sown wheat in Lesotho. The reaction of 55 South African and 18 foreign wheat cultivars was determined to pts. 6E16A- and 6E22A- in both the seedling and adult plant stage. The occurrence of stripe rust head infections was studied using 16 spring wheat cultivars and 17 supplemental lines. Six of the 55 local wheat cultivars expressed seedling resistance, 18 appeared heterogeneous and 31 were susceptible. The mean area under the disease progress curve (AUDPC) determined in the field for 42 cultivars over a three year period showed that 11 cultivars expressed high levels of complete or adult plant resistance (AUDPC <200). Twelve cultivars expressed intermediate levels of resistance (AUDPC 200 to 500) and 19 displayed AUDPC values of 500 to 1598. The percentage head infection was positively correlated to stripe rust severity on flag leaves. Of the 18 foreign cultivars evaluated 10 were resistant in both seedling and adult plant stages. The remaining eight cultivars were susceptible as seedlings but showed high levels of adult plant resistance in the field. Field trials were conducted from 1997 to 1999 to determine the effect of stripe and leaf rust (P. triticina Eriks.) epidemics on yield and quality of wheat. Five triazole fungicides, applied at two growth stages on three cultivars in the south Western Cape during 1997, resulted in a mean decrease of 31% in the AUDPC calculated for stripe rust infection. The application of fungicides closely to, or just after head emergence, resulted in a 65 to 74% decrease in the occurrence of stripe rust head infections. In contrast, head infection was reduced by only 8% when fungicides were applied at the seven leaf stage. Combined seven and flag leaf treatments with propiconazole, averaged over the three cultivars, resulted in a 56% yield increase, followed by increases of 49%, 44%, 39% and 25% with tebuconazole, flutriafol, bromuconazole, and flusllazole, respectively. In the absence of disease during 1998 no fungicide treatment resulted in a significant yield or hectolitre mass increase in any of the trials. The application of eight fungicides at both seven and flag leaf stages at Langgewens in the Western Cape during 1999, resulted in a mean decrease of 65% in the AUDPC, calculated for leaf rust severity. Combined seven and flag leaf treatments resulted in a mean yield increase of 56%, followed by 50 and 15% for the flag leaf and seven leaf treatments, respectively. Over treatments applied, yield increases varied from 24% for bromuconazole to 53% for epoxiconazole/carbendazim. Furthermore, the application of a flag leaf, and combined seven and flag leaf treatments, resulted in a significant increase in hectolitre mass. During 1999 the combination of triticonazole seed treatment with a propiconazole flag leaf spray on the cultivar Gariep in the eastern Free State resulted in a 91% decrease in the stripe rust AUDPC, and an associated 36% yield increase. Hectolitre mass increased by 3% and protein content decreased by 4% for the latter treatment. Triticonazole seed treatment had a 54% decrease in the AUDPC resulting in 16 and 2% yield and hectolitre mass increase, respectively. The best control of stripe rust was obtained with a combined seven and flag leaf treatment with propiconazole, as well as triticonazole seed treatment combined with a seven and flag leaf treatment of propiconazole. The latter two treatments resulted in a 49% yield increase. The results obtained in yield loss studies emphasise the importance of research aimed at the genetic control of rust diseases of wheat in South Africa. Effective and longlasting genetic control can only be obtained by coordinating future research, continuous monitoring of changes in the pathotype population, the regular collection of germ plasm carrying new or unused sources of resistance, characterising current sources of resistance, and by deploying available sources of resistance in a responsible manner. The result of successful genetic control is not only aimed at preventing the repeated application of fungicides, but also at reducing risk in wheat production, thereby ensuring more stable yields of high quality.

Afrikaans: Streeproes, veroorsaak deur Puccinia striiformis Westend. f. sp. tritici Eriks., het In endemiese siekte van koring (Triticum aestivum L.) in Suid-Afrika geword na die eerste waarneming daarvan naby Moorreesburg in die Wes-Kaap gedurende Augustus 1996. Patotipes (pts.) gevind in gereelde opnames was 6E16A- met virulensie vir Yr2,6,7,B, 11,14,17 en Yr19 en 6E22A- met bykomende virulensie vir Yr25. Streeproesisolate verkry vanaf Hordeum murinum L. in die Wes-Kaap is geïdentifiseer as pt. 6E16A-, terwyl beide pts. 6E16A- en 6E22A- geïdentifiseer is vanaf Bromus catharticus Vahl in die Oos-Vrystaat. Die moontlike rol wat grasspesies speel in die oorsomering van die streeproespatogeen kon nie volledig uitgeklaar word nie. Streeproesinfeksies is egter gevind op someraanplantings van koring in die suidelike Wes-Kaap gedurende 1998, asook gedurende 1998-2000 op opslagkoring in die somer- en herfsmaande in die Oos-Vrystaat, sowel as op someraanplantings van koring in Lesotho. Die reaksie van 55 Suid-Afrikaanse en 18 buitelandse koringkultivars is bepaal teen pts. 6E16A- en 6E22A- in die saailing- en volwasseplantstadiums. Die voorkoms van streeproesaarinfeksies is bestudeer deur gebruik te maak van 16 lentekoringkultivars en 17 bykomstige lyne. Ses van die 55 plaaslike kultivars het saailingweerstand getoon, 18 het heterogeen voorgekom en 31 was vatbaar. Die gemiddelde area onder die siekte-ontwikkelingskurwe (AOSOK), soos bepaal in die veld vir 42 kultivars oor In driejaar periode, het getoon dat 11 kultivars oor hoë vlakke van algehele of volwasseplantweerstand beskik (AOSOK <200). Twaalf kultivars het intermediêre vlakke van weerstand getoon (AOSOK 200 tot 500) met 19 kultivars waarvan die AOSOK tussen 500 en 1598 gevarieer het. Die persentasie aarinfeksie was positief gekorreleer met streeproesintensiteit op vlagblare. Van die 18 buitelandse kultivars was 10 weerstandbiedend in beide saailing- en volwasseplantstadiums. Die oorblywende agt kultivars was vatbaar as saailinge met hoë vlakke van volwasseplantweerstand in die veld. Veldproewe is uitgevoer vanaf 1997 tot 1999 om die effek van streep- en blaarroesepidemies (P. triticina Eriks.) op opbrengs en kwaliteit van koring te bepaal. Vyf triasoolswamdoders, toegedien tydens twee groeistadiums op drie kultivars in die suid Wes-Kaap gedurende 1997, het aanleiding gegee tot 'n 31% afname in die streeproes AOSOK. Die toediening van swamdoders, naby of net na aarverskyning, het 'n 65- tot 74% afname in die voorkoms van streeproes-aarinfeksies meegebring. In kontras hiermee het aarinfeksie met 8% afgeneem wanneer swamdoders slegs op die seweblaargroeistadium toegedien is. Gekombineerde sewe- en vlagblaarbehandelings met propikonasool, oor die drie kultivars, het 'n 56% opbrengstoename gerealiseer, gevolg deur opbrengsverhogings van 49%, 44%, 39% en 25% met tebukonasool, flutriafol, bromukonasool en flusilasool, onderskeidelik. In die afwesigheid van siekte gedurende 1998 kon geen swamdoderbehandeling 'n betekenisvolle opbrengs of hektolitermassaverhoging realiseer in enige van die proewe nie. Met die toediening van agt swamdoders op beide sewe- en vlagblaargroeistadiums op Langgewens in die Wes-Kaap gedurende 1999, is 'n gemiddelde afname van 65% in die blaarroes AOSOK verkry. Die resultaat van die gekombineerde sewe- en vlagblaartoedienings was 'n gemiddelde toename van 56% in opbrengs, gevolg deur 50% en 15% vir die vlagblaar- en seweblaartoedienings, onderskeidelik. Oor behandelings toegepas het opbrengstoenames gevarieer vanaf 24% vir bromukonasool tot 53% vir epoksikonasool/karbendasim. Die toediening van die vlagblaar- en gekombineerde sewe- en vlagblaartoedienings het 'n betekenisvolle toename in hektolitermassa gerealiseer. Gedurende 1999 het die kombinasie van 'n tritikonasool saadbehandeling met 'n propikonasool vlagblaarbehandeling op die kultivar Gariep in die Oos-Vrystaat 'n 91% afname in die AOSOK bereken vir streeproes teweeggebring, met 'n gevolglike 36% opbrengstoename. Hektolitermassa het toegeneem met 3% en proteïeninhoud het afgeneem met 4% vir laasgenoemde behandeling. Tritikonasool saadbehandeling het 'n 54% afname in die AOSOK tot gevolg gehad wat 16% en 2% opbrengs- en hektolitermassatoenames onderskeidelik teweeggebring het. Die beste beheer van streeproes is verkry met 'n gekombineerde sewe- en vlagblaarbehandeling van propikonasool, sowel as met tritikonasool saadbehandeling gekombineer met 'n sewe- en vlagblaartoediening van propikonasool. Laasgenoemde twee behandelings het in 'n 49% opbrengsverhoging gerealiseer. Oesverliesstudies het die belangrikheid van navorsing wat daarop gerig is om roessiektes van koring geneties te beheer in Suid-Afrika baie sterk beklemtoon. Effektiewe genetiese beheer kan slegs bereik word deur die koordinering van toekomstige navorsing, deur volgehou patogeenmonitering, die versameling van nuwe of onbenutte weerstandsbronne, die karaktarisering van bestaande weerstandsbronne, en deur beskikbare weerstand op 'n verantwoordelike wyse te ontplooi. Die resultaat van suksesvolle genetiese beheer het nie net ten doelom die herhaaldelike toediening van swamdoders te voorkom nie, maar ook om die risiko van koringverbouing te verlaag en om by te dra tot 'n meer stabiele jaarlikse opbrengs van hoë kwaliteit.
Keywords: Puccinia striiformis; Puccinia triticina; Stripe rust; Leaf rust; Pathotypes; Cultivar resistance; Chemical control; Seed treatment; Leaves -- Diseases and pests; Wheat rusts; Agricultural chemicals -- Foliar application; Thesis (Ph.D. (Plant Pathology))--University of the Free State, 2001